2019
DOI: 10.3390/plants8110483
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of HECT-E3 Ligases in Cell Senescence and Cell Death of Plants

Abstract: Plant cells undergo massive orderly changes in structure, biochemistry, and gene expression during cell senescence. These changes cannot be distinguished from the hydrolysis/degradation function controlled by the ubiquitination pathway, autophagy, and various hydrolases in cells. In this mini-review, we summarized current research progress that the human HECT (homologous to the E6AP carboxyl terminus)-type ubiquitin E3 ligases have non-redundant functions in regulating specific signaling pathways, involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 69 publications
(108 reference statements)
0
17
0
Order By: Relevance
“…Arabidopsis HECT-type ubiquitin ligase 5 (UPL5) is a member of the plant HECT-type ubiquitinated E3 ligase family, which is highly expressed in senescent leaves [ 9 ]. In comparing the amino acid sequences of animal and plant HECT-type ubiquitin ligases, it is found that there is no member corresponding to UPL5 of Arabidopsis HECT-type ubiquitinated E3 ligase family in yeast and animal genomes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis HECT-type ubiquitin ligase 5 (UPL5) is a member of the plant HECT-type ubiquitinated E3 ligase family, which is highly expressed in senescent leaves [ 9 ]. In comparing the amino acid sequences of animal and plant HECT-type ubiquitin ligases, it is found that there is no member corresponding to UPL5 of Arabidopsis HECT-type ubiquitinated E3 ligase family in yeast and animal genomes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin-protein ligase enzyme (E3) directly removes the damaged proteins through the degradation pathway and participates in the protein quality-control pathway. At the same time, it also removes damaged proteins, chloroplasts, and other organelles in batches by regulating the key factors of autophagy and cell death [ 33 , 34 , 35 ], and participates in cell death regulation. The DEGs of the three comparison groups were annotated to the E3 ligase enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitin and ubiquitin-like modification is a dynamic and reversible process involving the covalent attachment of a conserved 76-amino acid peptide ubiquitin (ub) to the ε-amino groups of lysine residues in target proteins. Ubiquitin addition is catalyzed by an enzymatic cascade involving an E1 ub-activating enzyme, followed by the sequential activities of E2 ub-conjugating enzyme and E3 ub ligase (Smalle and Vierstra, 2004 ; Lan and Miao, 2019 ). This process is reversible as a result of deubiquitinating enzymes (DUBs).…”
Section: The Regulation Of As Through Ptmsmentioning
confidence: 99%